2015
DOI: 10.1007/s10592-015-0735-z
|View full text |Cite
|
Sign up to set email alerts
|

Population genetics of the diamondback terrapin, Malaclemys terrapin, in Louisiana

Abstract: Previous population genetic studies of diamondback terrapins (Malaclemys terrapin) have typically focused on either the entire range or relatively small spatial scales. The Louisiana coastline contains vast salt marshes suitable for terrapins; however, two major freshwater inputs (Atchafalaya River and Mississippi River Deltas) break up the seemingly contiguous habitat and may isolate populations of terrapins. To determine population genetic structure and connectivity of terrapins occupying Louisiana marshes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
4
2
0
Order By: Relevance
“…Overall estimates of genetic diversity based on microsatellite data (average Hs = 0.55) were similar to values estimated for Elseya albagula, an endangered freshwater turtle co-distributed with MRT (average Hs = 0.57; Todd et al, 2013), but lower than values observed in a range of other threatened turtle species (Davy, Bernardo, & Murphy, 2014;Escalona et al, 2009;Petre, Selman, Kreiser, Pearson, & Wiebe, 2015). The low microsatellite-based estimate of heterozygosity (Hs = 0.55) found in MRTs is close to the threshold of 0.54 identified by Willoughby et al (2015) as symptomatic of a species that merits conservation concern as Critically Endangered.…”
Section: Genetic Divergence Between Tinana and Mary Subpopulations Wassupporting
confidence: 69%
See 2 more Smart Citations
“…Overall estimates of genetic diversity based on microsatellite data (average Hs = 0.55) were similar to values estimated for Elseya albagula, an endangered freshwater turtle co-distributed with MRT (average Hs = 0.57; Todd et al, 2013), but lower than values observed in a range of other threatened turtle species (Davy, Bernardo, & Murphy, 2014;Escalona et al, 2009;Petre, Selman, Kreiser, Pearson, & Wiebe, 2015). The low microsatellite-based estimate of heterozygosity (Hs = 0.55) found in MRTs is close to the threshold of 0.54 identified by Willoughby et al (2015) as symptomatic of a species that merits conservation concern as Critically Endangered.…”
Section: Genetic Divergence Between Tinana and Mary Subpopulations Wassupporting
confidence: 69%
“…Likewise, the timescale of divergence between Tinana and Mary populations of Australian lungfish is relatively recent (less than 10,000 years) and linked to periods of lowered sea level in the late Pleistocene(Bishop et al, in press).Overall estimates of genetic diversity based on microsatellite data (average Hs = 0.55) were similar to values estimated for Elseya albagula, an endangered freshwater turtle co-distributed with MRT (average Hs = 0.57;Todd et al, 2013), but lower than values observed in a range of other threatened turtle species(Davy, Bernardo, & Murphy, 2014;Escalona et al, 2009;Petre, Selman, Kreiser, Pearson, & Wiebe, 2015). Lack of phylogeographic mtDNA divergence in MRTs indicates that the Tinana-Mary barrier is not an old one.…”
mentioning
confidence: 55%
See 1 more Smart Citation
“…With the exception of some studies that present low genetic diversity (value of H e < 0.4; [6869]), freshwater turtles exhibit high values of genetic diversity (generally H e > 0.6-0.7; see Table 4 in [69] for examples, and [70]) based on microsatellites. Our values could be considered lower ( H e < 0.6) than many other freshwater turtles or even threatened species (see Table 4 in [69] for examples, and [7071]), and are in agreement with values for wild populations of Elusor macrurus Cann & Legler 1994 (Testudines, Chelidae) an endangered Australian freshwater turtle [72]. The sole genetic study that reports value of genetic diversity for Trachemys spp.…”
Section: Discussionsupporting
confidence: 79%
“…With the exception of some studies that present low genetic diversity (value of H e < 0.4; Echelle et al., 2010; Vargas-Ramírez et al., 2012), freshwater turtles generally exhibit high values of genetic diversity (generally H e > 0.6–0.7; Vargas-Ramírez et al., 2012, Table 4 for examples; Davy et al., 2014) when using methodology based on microsatellites. Our values could be considered lower ( H e < 0.6) than many other freshwater turtles or even threatened species (Davy et al., 2014; Petre et al., 2015; Vargas-Ramírez et al., 2012, Table 4 for examples), and correspond with values for wild populations of Elusor macrurus Cann & Legler 1994 (Testudines, Chelidae) an endangered Australian freshwater turtle (Schmidt et al., 2018). Very few studies report values of genetic diversity for Trachemys spp.…”
Section: Discussionsupporting
confidence: 54%